SISTEM KEAMANAN PERUMAHAN BERBASIS MIKROKONTROLER ARDUINO UNO - Andini Dani Achmad; Zaryanti Zainuddin (Universitas Fajar, 2016)
This research was aimed at staking out a residential security system with simulation using microcontroller Arduino. Uno and test the residential security. This tools using Sensor PIR for detect Human movement in house and GSM Modem for sending a short message in n movement willgive a dangerous signal to GSM Modem. Then GSM Modem will be sending a short message for owner of the phone